to solve 5/8(x - 1/2)= 10, the first step is

  1. Consider the sequence of steps to solve the equation:5(x-3)=7x/2 Step 1 = 10(x - 3) = 7x Step 2 = 10x - 30 = 7x Step 3 = 3x - 30
    1. answers icon 1 answer
    2. views icon 140 views
  2. Consider the sequence of steps to solve the equation:5(x - 3) = Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x
    1. answers icon 1 answer
    2. views icon 20 views
  3. Consider the sequence of steps to solve the equation:5(x - 3) = Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x
    1. answers icon 1 answer
    2. views icon 78 views
  4. Consider the sequence of steps to solve the equation:5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 1 answer
    2. views icon 258 views
  5. Consider the sequence of steps to solve the equation:5(x - 3) = 7x/2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 1 answer
    2. Sarah B asked by Sarah B
    3. views icon 59 views
  6. Consider the sequence of steps to solve the equation:5(x - 3) = 7x/2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 1 answer
    2. views icon 20 views
  7. Consider the sequence of steps to solve the equation:5(x - 3) = 7x/2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 1 answer
    2. views icon 22 views
  8. Consider the sequence of steps to solve the equation:5(x - 3) = 7x/2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 1 answer
    2. views icon 110 views
  9. Consider the sequence of steps to solve the equation:5(x - 3) = 7x/2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 1 answer
    2. views icon 21 views
  10. Consider the sequence of steps to solve the equation:5(x - 3) = 7x/2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 1 answer
    2. diggergaming asked by diggergaming
    3. views icon 92 views